Efeitos da Implementação do Piso Salarial Profissional Nacional na carreira dos docentes da Rede Estadual de Ensino de Minas Gerais: subsídio e sistema unificado de remuneração - Clayton Lucio Coelho (2016)
This dissertation presents a study about the modifications occurred on the plan of career and remuneration of basic educations professionals from Rede Estadual de Ensino de Minas Gerais since 2008, when the enactment of the Law nº. 11.738/2008 (BRASIL, 2008), that instituted the National Minimum Wage for Professionals of the public mastership of basic education. Such modifications occurred in a sharp way in 2010, when the State Project Law that instituted the subside as a form of payment to public servers was approved, in addition to deploy structural changes in teachers career. In the following year, 2011, another State Project Law gave origin to the Unified System of Remuneration, thus promoting definitive repositioning of the servers in terms of career and payment of the National Minimum Wage in a definitive way of subside to teachers and specialists in installments, until 2015. The research was fulfilled by documental survey in files available in Assembleia Legislativa do Estado de Minas Gerais, Sindicato Único dos Trabalhadores em Educação de Minas Gerais and govern institutes from Minas Gerais state, besides interviews with actors involved in the process of implementation of National Minimum Wage in teachers career from Rede Estadual de Ensino de Minas Gerais. The technique used was the analysis of content, which let the conclusion that the Minas Gerais Government, to implement the National Minimum Wage under the form of a subside, promoted expressive changes in the teacher career structure, with the reduction of levels of promotion and progression. The end of the possibilities to acquire gratifications, benefits and advantages resulted from time in service. Besides the repositioning of the older servers to the beginning of the career, creating discontent, lost of wage and guarantees previously instituted.